p16INK4a Expression and Absence of Activated B-RAF Are Independent Predictors of Chemosensitivity in Melanoma Tumors - Stuart J. Gallagher; John F. Thompson; James Indsto; Lyndee L. Scurr; Margaret Lett; Bo-Fu Gao; Ruth Dunleavey; Graham J. Mann; Richard F. Kefford; Helen Rizos (Neoplasia: An International Journal for Oncology Research, 2008)
Metastatic cutaneous melanoma is highly resistant to cytotoxic drugs, and this contributes to poor prognosis. In vivo studies on the chemosensitivity of metastatic melanoma are rare and hampered by poor response rates to systemic chemotherapeutics. Patients who undergo isolated limb infusion (ILI) with cytotoxic drugs show high response rates and are, therefore, a good cohort for studying chemosensitivity in vivo. We used tumors from patients who underwent ILI to study the role of melanoma tumor-suppressor genes and oncogenes on melanoma chemosensitivity. Prospectively acquired tumors from 30 patients who subsequently underwent ILI with melphalan and actinomycin-D for metastatic melanoma were investigated for mRNA expression levels of p14ARF, p16INK4a, and MITFm. The mutation status of B-RAF, N-RAS, and PTEN were also determined. A high percentage of tumors had activating mutations in either B-RAF (15/30) or N-RAS (10/30) and only two tumors carried altered PTEN. High expression of p16INK4a and absence of an activating B-RAF mutation independently predicted response to treatment. Further, inducible expression of p16INK4a sensitized a melanoma cell line to death induced by melphalan or actinomycin-D. This study shows that high expression of p16INK4a or the absence of activated B-RAF correlates with in vivo response of melanoma to cytotoxic drugs.